Sludge dewatering conditioning method

By preparing modified carboxymethyl starch and modified perlite, a sludge conditioner is formed, which solves the problems of Fe2+ oxidation and Fe3+ treatment, achieves the stable release and recycling of Fe2+ in the sludge, and significantly improves the sludge dehydration effect. .

CN119330565AInactive Publication Date: 2025-01-21ANJIEYU BEIJING OILFIELD TECHNICAL SERVICES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411404608.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing sludge dewatering technology, Fe2+ is easily oxidized to Fe3+, resulting in a decrease in the concentration of sulfate radicals and a worsening effect of sludge dewatering; at the same time, the by-product Fe3+ is difficult to effectively treat, which increases the disposal cost.

Method used

By preparing modified carboxymethyl starch and modified perlite, a sludge conditioner is formed, the modified carboxymethyl starch is used to increase the complexing amount of Fe2+, and 3,4-dihydroxybenzoic acid is used to quickly complex and reduce Fe3+ , converted into Fe2+ to realize its recycling.

Benefits of technology

The concentration and existence time of Fe2+in the sludge is increased, FE2+is stable, which significantly improves the darling effect of the sludge, reduces the cost of transportation, and effectively handles the by -products FE3+.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a sludge dewatering conditioning method, and belongs to the technical field of sludge treatment.The preparation method comprises the steps of sludge conditioner preparation, sludge conditioning and filter pressing dewatering; the sludge conditioning comprises the following steps: adding modified carboxymethyl starch into deionized water, uniformly stirring, then adding modified perlite powder, uniformly stirring for 40-60 minutes, filtering, adding a filter cake into a FeSO4 solution, stirring for 1.5-2.2 hours, standing for 25-35 minutes, filtering, drying the filter cake to obtain a product modified perlite loaded Fe < 2 + > / modified carboxymethyl starch complex, namely a sludge conditioning agent, adjusting the pH value of sludge to 4-8.5, and drying to obtain the sludge conditioning agent. The method comprises the following steps: adding a sludge conditioner, 3, 4-dihydroxybenzoic acid and a Na2SO3 solution into sludge, stirring, reacting for 50-70 minutes, and carrying out filter pressing dehydration; according to the sludge dewatering conditioning method, the cracking rate of extracellular polymeric substances of the sludge is high, the sludge dewatering rate is high, the water content of a sludge cake is 50.8-54.2%, and the specific resistance of the sludge is as low as 6.38 * 10 < 11 >-6.79 * 10 < 11 > m / kg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sludge treatment, and in particular relates to a sludge dehydration conditioning method. Background Art

[0002] Sludge is an inevitable product of sewage treatment, and its production volume is increasing day by day. How to economically and effectively treat and comprehensively utilize sludge as a resource has become the focus and difficulty of current research.

[0003] As a necessary step in sludge treatment, dehydration can minimize the volume of sludge and reduce its transportation costs, and is a key step in achieving sludge reduction, harmlessness and resource utilization. However, sludge has extracellular polymers formed by the ionization of negatively charged functional groups, which can maintain a stable hydrated colloidal structure to prevent the release of water, which is a key factor causing the difficulty of sludge dehydration.

[0004] In recent years, advanced oxidation processes based on sulfate free radicals have been gradually applied to sludge dewatering. By adding persulfate or sulfite as a raw material for providing sulfate free radicals to the sludge to be treated, and adding an activator, sulfate free radicals can be generated in the sludge. Sulfate free radicals have a high efficiency in breaking down extracellular polymers and react quickly, thereby releasing a large amount of bound water in the sludge and improving the sludge dewatering effect.

[0005] Fe 2+ Activators (one or more ferrous salts, such as ferrous sulfate, ferrous chloride, ferrous carbonate, etc.) are cheap, readily available, environmentally friendly, and have the most obvious activation effect. They are most widely used in the field of sludge dewatering. However, (1) Fe 2+ Easily oxidized to Fe 3+ , resulting in Fe 2+ As the concentration decreases, the activation rate of persulfate or sulfite decreases, which in turn leads to a decrease in the concentration of the product sulfate radical, a decrease in the efficiency of breaking down extracellular polymers in sludge, and a poorer sludge dewatering effect. (2) If Fe is increased 2+ Dosage, excess Fe 2+ It will also consume the product sulfate free radicals, thereby reducing the oxidation efficiency of sulfate free radicals and worsening the sludge dewatering effect. (3) Fe 2+ The byproduct of the reaction with persulfate or sulfite is Fe 3+ , Fe 3+ It is easy to precipitate and form iron sludge, which increases the disposal cost.

[0006] Patent CN113072286A discloses a sludge conditioning method for improving the dewatering capacity of sludge, wherein citric acid is mixed with Fe 2+ Complexation, protection of Fe 2+ Not oxidized, Fe 2+Activated persulfate produces sulfate free radicals, which are used to degrade extracellular polymers in sludge, thereby improving the sludge dewatering effect. 2+ The complex is not stable enough and is easily affected by the external environment (temperature, pressure, pH value, etc.), which makes it impossible to stably maintain the Fe 2+ The concentration of byproduct Fe 3+ No effective processing was carried out. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a sludge dewatering conditioning method to achieve the following invention objectives: to increase the content of Fe 2+ The complex of Fe 2+ The complexing amount of Fe 2+ The complex can stably release Fe 2+ , the by-product Fe 3+ Converted to Fe 2+ Recycle and improve sludge dewatering effect.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A sludge dehydration conditioning method comprises the following steps: 1. Preparation of modified carboxymethyl starch Add carboxymethyl starch to the NaOH solution and stir until the solution becomes transparent. Then add acrylic acid, hydroxypropyl acrylate, and diacetone acrylamide in sequence. Stir thoroughly for 10 to 20 minutes after adding each reagent. The stirring rate is 75 to 85 r / min. Finally, place the mixture in a 60 In a Coγ irradiation device, radiation polymerization is carried out at an absorbed dose of 4 to 6 kGy for 30 to 40 minutes, and after the polymerization is completed, the modified carboxymethyl starch is dried in a constant temperature box at 70 to 90° C. for 35 to 45 minutes to obtain the modified carboxymethyl starch; The mass fraction of the NaOH solution is 32-38%; The mass ratio of the NaOH solution to the carboxymethyl starch is 115-125:0.8-1.2; The mass ratio of the carboxymethyl starch, acrylic acid, hydroxypropyl acrylate and diacetone acrylamide is 0.8-1.2:10-12:1.70-1.80:1.6-2.0; The modified carboxymethyl starch can greatly improve the Fe 2+ complexing capacity.

[0009] 2. Preparation of modified perlite The perlite is dried at a temperature of 350-450°C for 10-20 minutes, and then preheated at 940-960°C for 15-25 seconds, and then heated at 1100-1200°C for 1.5-2.5 minutes, and then cooled to obtain expanded perlite. The expanded perlite is ground into a powder with a particle size of 0.1-0.2 mm, and then added to a NaOH solution, soaked for 25-35 minutes, and then Al2O3 is added. After stirring evenly, the solution is heated at a constant temperature of 60-80°C for 3-5 hours, cooled to room temperature, and the obtained solid product is rinsed with deionized water, placed in a constant temperature drying oven at 80-100°C for 0.8-1 hour, and ground into a powder with a particle size of 0.05-0.12 mm to obtain modified perlite.

[0010] The mass fraction of the NaOH solution is 20-30%; The Al2O3 particle size is 0.3-0.5 mm; The mass ratio of the expanded perlite, NaOH solution and Al2O3 is 0.9-1.1:8-12:1.5-1.7; The modified perlite is heated and expanded to increase the number and size of the internal pores of the perlite, thereby increasing the loading capacity of the perlite for carboxymethyl starch; the expanded perlite is soaked in NaOH and mixed with Al2O3 for heating, thereby changing the ratio of silicon and aluminum, the main components of the expanded perlite, and thus increasing the loading capacity of the perlite for Fe 2+ Ion exchange capacity; The ratio of silicon to aluminum can be controlled by adjusting the concentration and immersion time of NaOH, the amount of Al2O3 added, the heating time and the temperature.

[0011] 3. Preparation of sludge conditioner Add the modified carboxymethyl starch into deionized water, stir for 8-12 minutes to completely dissolve it, then add the modified perlite with a particle size of 0.05-0.12 mm, stir evenly, so that the modified carboxymethyl starch is evenly attached to the modified perlite, filter after 40-60 minutes, add the filter cake into the freshly prepared FeSO4 solution, stir for 1.5-2.2 hours, the stirring rate is 60-70 r / min, let it stand for 25-35 minutes, filter, and dry the filter cake in a constant temperature box at 45-55°C for 18-24 minutes to obtain the modified perlite loaded Fe 2+ / modified carboxymethyl starch complex, i.e. sludge conditioner; The mass ratio of the modified carboxymethyl starch, deionized water, modified perlite, and FeSO4 solution is 0.8-1.2: 400-600: 1.9-2.1: 20-24; The mass fraction of the FeSO4 solution is 20-30%.

[0012] 4. Sludge conditioning Take a certain mass of sludge (water content 95%), adjust its pH value to 4-8.5 with dilute sulfuric acid, then add sludge conditioner and 3,4-dihydroxybenzoic acid to the sludge, stir for 8-12 minutes, add Na2SO3 solution, react for 50-70 minutes to obtain conditioned sludge; The mass ratio of the sludge, sludge conditioner, 3,4-dihydroxybenzoic acid and Na2SO3 solution is 400-420: 0.8-1.2: 2.7-2.8: 3.5-4.0; The mass fraction of the Na2SO3 solution is 28-35%; The concentration of the dilute sulfuric acid is 0.0.8-0.12 mol / L; The stirring rate is 45-55 r / min.

[0013] 5. Filter pressing and dehydration The conditioned sludge is filtered, and the pressure is kept stable at 0.40-0.50 MPa during the filtering process. After 7-9 minutes, the mud cake is taken out.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. Modified perlite loaded with Fe 2+ / After modified carboxymethyl starch complex, it has strong stability in sludge and is effective for Fe 2+ The complexing capacity is large, and it can release Fe at a certain rate over a long period of time. 2+ ; 3,4-dihydroxybenzoic acid can quickly complex Fe generated in sludge 3+ , and releases Fe by its own reduction reaction 2+ , increasing the Fe content in sludge 2+ Concentration and existence time of Fe 2+ The concentration was kept stable at 2.85~3.20mmol L -1 .

[0015] 2. The conditioning method of the present invention can quickly dehydrate the sludge. The moisture content of the conditioned sludge cake is as low as 50.8-54.2%, and the sludge specific resistance is 6.38×10 11 ~6.79×10 11 m / kg. DETAILED DESCRIPTION

[0016] Example 1 1. Preparation of modified carboxymethyl starch Add carboxymethyl starch to the NaOH solution and stir until the solution becomes transparent. Then add acrylic acid, hydroxypropyl acrylate, and diacetone acrylamide in sequence. Stir each time for 15 minutes at a stirring rate of 80 r / min. Finally, place the mixture in a 60 In a Coγ irradiation device, the polymerized product was irradiated for 35 min at an absorbed dose of 5 kGy, and after the polymerization was completed, the product was dried in a thermostat at 80°C for 40 min to obtain the modified carboxymethyl starch. The mass fraction of the NaOH solution is 35%; The mass ratio of the NaOH solution to the carboxymethyl starch is 120:1; The mass ratio of the carboxymethyl starch, acrylic acid, hydroxypropyl acrylate and diacetone acrylamide is 1:11:1.75:1.8.

[0017] 2. Preparation of modified perlite The perlite was dried at 400°C for 15 minutes, then preheated at 950°C for 20 seconds, heated at 1150°C for 2 minutes, and cooled to obtain expanded perlite. The expanded perlite was ground into a powder with a particle size of 0.15 mm and added to a NaOH solution. After soaking for 30 minutes, Al2O3 was added, stirred evenly, and heated at a constant temperature of 70°C for 4 hours. After cooling to room temperature, the obtained solid product was rinsed with deionized water, placed in a 90°C constant temperature drying oven for 0.9 hours, and ground into a powder with a particle size of 0.07-0.10 mm to obtain modified perlite. The mass fraction of the NaOH solution is 25%; The Al2O3 particle size is 0.4 mm; The mass ratio of the expanded perlite, NaOH solution and Al2O3 is 1:10:1.6.

[0018] 3. Preparation of sludge conditioner Add the modified carboxymethyl starch into deionized water, stir for 10 minutes to completely dissolve it, then add the modified perlite with a particle size of 0.07-0.10 mm, stir evenly, so that the modified carboxymethyl starch is evenly attached to the modified perlite. After 50 minutes, filter, add the filter cake into the freshly prepared FeSO4 solution, stir for 2 hours, the stirring rate is 65r / min, let it stand for 30 minutes, filter, and dry the filter cake in a 50℃ constant temperature box for 20 minutes to obtain the modified perlite loaded Fe 2+ / modified carboxymethyl starch complex, i.e. sludge conditioner; The mass ratio of the modified carboxymethyl starch, deionized water, modified perlite, and FeSO4 solution is 1:500:2:22; The mass fraction of the FeSO4 solution is 25%.

[0019] 4. Sludge conditioning Take a certain mass of sludge (water content 95%), adjust its pH value to 6 with dilute sulfuric acid, then add sludge conditioner and 3,4-dihydroxybenzoic acid to the sludge, stir for 10 minutes, add Na2SO3 solution, react for 60 minutes to obtain conditioned sludge; The mass ratio of the sludge, sludge conditioner, 3,4-dihydroxybenzoic acid and Na2SO3 solution is 410:1:2.74:3.7; The mass fraction of the Na2SO3 solution is 30%; The concentration of the dilute sulfuric acid is 0.1 mol / L; The stirring rate is 50 r / min.

[0020] 5. Filter pressing and dehydration The conditioned sludge was filtered, and the pressure was kept stable at 0.45MPa during the filtering process. After 8 minutes, the sludge dehydrated mud cake was obtained.

[0021] Example 2 1. Preparation of modified carboxymethyl starch Add carboxymethyl starch to the NaOH solution and stir until the solution becomes transparent. Then add acrylic acid, hydroxypropyl acrylate, and diacetone acrylamide in sequence. Stir each time for 10 minutes at a stirring rate of 75 r / min. Finally, place the mixture in a 60 In a Coγ irradiation device, radiation polymerization was carried out at an absorbed dose of 4 kGy for 30 minutes, and after the polymerization was completed, the modified carboxymethyl starch was dried in a 70°C constant temperature box for 35 minutes; The mass fraction of the NaOH solution is 32%; The mass ratio of the NaOH solution to the carboxymethyl starch is 115:0.8; The mass ratio of the carboxymethyl starch, acrylic acid, hydroxypropyl acrylate and diacetone acrylamide is 0.8:10:1.70:1.6.

[0022] 2. Preparation of modified perlite The perlite was dried at 350°C for 10 minutes, then preheated at 940°C for 15 seconds, and then heated at 1100°C for 1.5 minutes. After cooling, the expanded perlite was obtained. The expanded perlite was ground into a powder with a particle size of 0.1 mm and added to a NaOH solution. After soaking for 25 minutes, Al2O3 was added. After stirring evenly, the mixture was heated at a constant temperature of 60°C for 3 hours, cooled to room temperature, and the obtained solid product was rinsed with deionized water, placed in a constant temperature drying oven at 80°C for 0.8 hours, and ground into a powder with a particle size of 0.05-0.07 mm to obtain modified perlite. The mass fraction of the NaOH solution is 20%; The Al2O3 particle size is 0.3 mm; The mass ratio of the expanded perlite, NaOH solution and Al2O3 is 0.9:8:1.5.

[0023] 3. Preparation of sludge conditioner Add the modified carboxymethyl starch into deionized water, stir for 8 minutes to completely dissolve it, then add the modified perlite with a particle size of 0.05-0.07 mm, stir evenly, so that the modified carboxymethyl starch is evenly attached to the modified perlite. After 40 minutes, filter, add the filter cake into the freshly prepared FeSO4 solution, stir for 1.5 hours, the stirring rate is 60r / min, stand for 25 minutes, filter, and dry the filter cake in a 45℃ constant temperature box for 18 minutes to obtain the modified perlite loaded Fe 2+ / modified carboxymethyl starch complex, i.e. sludge conditioner; The mass ratio of the modified carboxymethyl starch, deionized water, modified perlite, and FeSO4 solution is 0.8:400:1.9:20; The mass fraction of the FeSO4 solution is 20%.

[0024] 4. Sludge conditioning Take a certain mass of sludge (water content 95%), adjust its pH value to 4 with dilute sulfuric acid, then add sludge conditioner and 3,4-dihydroxybenzoic acid to the sludge, stir for 8 minutes, add Na2SO3 solution, react for 50 minutes to obtain conditioned sludge; The mass ratio of the sludge, sludge conditioner, 3,4-dihydroxybenzoic acid and Na2SO3 solution is 400:0.8:2.7:3.5; The mass fraction of the Na2SO3 solution is 28%; The concentration of the dilute sulfuric acid is 0.08 mol / L; The stirring rate is 45 r / min.

[0025] 5. Filter pressing and dehydration The conditioned sludge was filtered, and the pressure was kept stable at 0.40MPa during the filtering process. After 7 minutes, the sludge dehydrated mud cake was obtained.

[0026] Example 3 1. Preparation of modified carboxymethyl starch Add carboxymethyl starch to the NaOH solution and stir until the solution becomes transparent. Then add acrylic acid, hydroxypropyl acrylate, and diacetone acrylamide in sequence. Stir each time for 20 minutes at a stirring rate of 85 r / min. Finally, place the mixture in a 60In a Coγ irradiation device, radiation polymerization was carried out at an absorbed dose of 6 kGy for 40 minutes, and after the polymerization was completed, the modified carboxymethyl starch was dried in a 90°C constant temperature box for 45 minutes; The mass fraction of the NaOH solution is 38%; The mass ratio of the NaOH solution to the carboxymethyl starch is 125:1.2; The mass ratio of the carboxymethyl starch, acrylic acid, hydroxypropyl acrylate and diacetone acrylamide is 1.2:12:1.80:2.0.

[0027] 2. Preparation of modified perlite The perlite was dried at 450°C for 20 minutes, then preheated at 960°C for 25 seconds, heated at 1200°C for 2.5 minutes, and cooled to obtain expanded perlite. The expanded perlite was ground into a powder with a particle size of 0.2 mm and added to a NaOH solution. After soaking for 35 minutes, Al2O3 was added, stirred evenly, and heated at 80°C for 5 hours. After cooling to room temperature, the obtained solid product was rinsed with deionized water, placed in a 100°C constant temperature drying oven and dried for 1 hour, and ground into a powder with a particle size of 0.10-0.12 mm to obtain modified perlite. The mass fraction of the NaOH solution is 30%; The Al2O3 particle size is 0.5 mm; The mass ratio of the expanded perlite, NaOH solution and Al2O3 is 1.1:12:1.7.

[0028] 3. Preparation of sludge conditioner Add the modified carboxymethyl starch into deionized water, stir for 12 minutes to completely dissolve it, then add the modified perlite with a particle size of 0.10-0.12 mm, stir evenly, so that the modified carboxymethyl starch is evenly attached to the modified perlite. After 60 minutes, filter, add the filter cake into the freshly prepared FeSO4 solution, stir for 2.2 hours, the stirring rate is 70r / min, stand for 35 minutes, filter, and dry the filter cake in a 55℃ constant temperature box for 24 minutes to obtain the modified perlite loaded Fe 2+ / modified carboxymethyl starch complex, i.e. sludge conditioner; The mass ratio of the modified carboxymethyl starch, deionized water, modified perlite, and FeSO4 solution is 1.2:600:2.1:24; The mass fraction of the FeSO4 solution is 30%.

[0029] 4. Sludge conditioning Take a certain mass of sludge (water content 95%), adjust its pH value to 8.5 with dilute sulfuric acid, then add sludge conditioner and 3,4-dihydroxybenzoic acid to the sludge, stir for 12 minutes, add Na2SO3 solution, react for 70 minutes to obtain conditioned sludge; The mass ratio of the sludge, sludge conditioner, 3,4-dihydroxybenzoic acid and Na2SO3 solution is 420:1.2:2.8:4.0; The mass fraction of the Na2SO3 solution is 35%; The concentration of the dilute sulfuric acid is 0.12 mol / L; The stirring rate is 55 r / min.

[0030] 5. Filter pressing and dehydration The conditioned sludge was filtered, and the pressure was kept stable at 0.50MPa during the filtering process. After 9 minutes, the sludge dehydrated mud cake was obtained.

[0031] Comparative Example 1 In order to verify the effect of modified carboxymethyl starch, the same sludge dehydration conditioning method as in Example 1 was used, except that carboxymethyl starch was directly used in step 1 without modification, and modified carboxymethyl starch was replaced by carboxymethyl starch in step 3.

[0032] Comparative Example 2 In order to verify the effect of modified perlite, the same sludge dehydration conditioning method as in Example 1 was used, except that step 2 was omitted, and the addition of modified perlite was omitted in step 3. Specifically, modified carboxymethyl starch was added to 600 ml of deionized water, stirred for 10 min to completely dissolve it, and then added to the freshly prepared FeSO4 solution, stirred for 2 h, allowed to stand for 30 min, filtered, and the filter cake was dried in a 50°C thermostat for 20 min to obtain FeSO4. 2+ / modified carboxymethyl starch complex.

[0033] The mass ratio of the modified carboxymethyl starch to the FeSO4 solution is 1:22; The mass fraction of the FeSO4 solution is 25%; The stirring rate is 65 r / min.

[0034] Comparative Example 3 In order to verify the effect of 3,4-dihydroxybenzoic acid, the same sludge dehydration conditioning method as in Example 1 was adopted, except that the addition of 3,4-dihydroxybenzoic acid in step 3 was omitted.

[0035] Test Example 1 The moisture content of the sludge cakes after dehydration of the sludge in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the test method was as follows: The dehydrated sludge cakes of Examples 1 to 3 and Comparative Examples 1 to 3 were placed in a drying oven in turn, and the temperature was controlled at 100 to 110°C. After the mass of the sludge cakes was constant, the mass of the sludge cakes before and after drying was measured, and the moisture content of the sludge cakes was calculated. The mass of the sludge cakes before drying was recorded as m1, and the mass of the sludge cakes after drying was recorded as m2. The formula for calculating the moisture content of the sludge cakes is as follows:

[0036] The test results are shown in Table 1.

[0037] Table 1

[0038] Test Example 2 Taking the addition of Na2SO3 solution in step 4 of Examples 1 to 3 and Comparative Examples 1 to 3 as the starting time, the Fe content in the sludge was measured at different time periods (5, 10, 20, 40, 50 and 60 min). 2+ The concentration test is as follows: Take the addition of Na2SO3 solution in step 4 of Examples 1 to 3 and Comparative Examples 1 to 3 as the starting time, make corresponding labels for the sludge at different time periods (5, 10, 20, 40, 50 and 60 min), turn on the iron ion analyzer, calibrate it, immerse the sensor probe in the sludge to be tested in turn, and measure the Fe in the sludge at different time periods. 2+ The concentration was recorded and the test results are shown in Table 2: Table 2

[0039] Test Example 3 The sludge specific resistance test was performed on the sludge conditioned in step 4 of Examples 1 to 3 and Comparative Examples 1 to 3. The test method adopted the conventional Buchner funnel method. The results are shown in Table 3.

[0040] Table 3

[0041] It can be seen from the above results that compared with Comparative Examples 1, 2, and 3, Example 1 has a lower moisture content in the mud cake and a lower sludge specific resistance. 2+ Able to maintain a relatively stable and high concentration.

[0042] Further, in Comparative Example 1, carboxymethyl starch was not modified, and carboxymethyl starch was modified to Fe 2+ The complexing capacity of Fe in sludge is low. 2+ The concentration is low; Comparative Example 2: No modified perlite was used to load Fe 2+ / Modified carboxymethyl starch complex, Fe 2+ / Modified carboxymethyl starch complex has low stability and is greatly affected by factors in sludge (temperature, pressure, pH, etc.), which leads to Fe 2+ The concentration in the sludge is high, fluctuates greatly, and is consumed too quickly; Comparative Example 3 did not add 3,4-dihydroxybenzoic acid, and the byproduct Fe 3+ No reduction recycling is performed, resulting in Fe 2+ Without replenishment, the concentration drops rapidly; In summary, in Comparative Examples 1, 2, and 3, Fe 2+ The concentration is lower, so the sulfate radicals produced by activated sodium sulfite are less, which in turn leads to a decrease in the efficiency of the sludge external polymer, and an increase in the sludge moisture content and sludge specific resistance.

Claims

1. A sludge dehydration conditioning method, characterized in that: The preparation method comprises preparing a sludge conditioner, sludge conditioning, and filter pressing and dehydration; The method for preparing the sludge conditioner comprises adding modified carboxymethyl starch into deionized water, stirring to completely dissolve it, then adding modified perlite powder with a particle size of 0.05 to 0.12 mm, stirring evenly, filtering after 40 to 60 minutes, adding the filter cake into a freshly prepared FeSO4 solution, stirring for 1.5 to 2.2 hours, standing for 25 to 35 minutes, filtering, and drying the filter cake to obtain a modified perlite loaded Fe 2+ / Modified carboxymethyl starch complex, i.e. sludge conditioner.

2. A sludge dewatering and conditioning method according to claim 1, characterized in that: In the step of preparing the sludge conditioner, the mass ratio of modified carboxymethyl starch, deionized water, modified perlite and FeSO4 solution is 0.8-1.2:400-600:1.9-2.1:20-24; the mass fraction of the FeSO4 solution is 20-30%.

3. A sludge dewatering and conditioning method according to claim 1, characterized in that: The preparation method of the modified carboxymethyl starch is to add the carboxymethyl starch to the NaOH solution, stir until transparent, then add acrylic acid, hydroxypropyl acrylate and diacetone acrylamide in sequence, and place the mixture in a 60 In a Coγ irradiation device, after irradiation polymerization for 30 to 40 minutes at an absorbed dose of 4 to 6 kGy, the polymer is dried to obtain modified carboxymethyl starch.

4. A sludge dewatering and conditioning method according to claim 3, characterized in that: In the preparation step of the modified carboxymethyl starch, the mass ratio of carboxymethyl starch, NaOH solution, acrylic acid, hydroxypropyl acrylate and diacetone acrylamide is 0.8-1.2:115-125:10-12:1.70-1.80:1.6-2.0; and the mass fraction of the NaOH solution is 32-38%.

5. A sludge dewatering and conditioning method according to claim 1, characterized in that: The preparation method of the modified perlite comprises the following steps: drying the perlite, preheating the perlite at 940-960° C. for 15-25 seconds, heating the perlite at 1100-1200° C. for 1.5-2.5 minutes, cooling the perlite to obtain expanded perlite, grinding the expanded perlite into a powder with a particle size of 0.1-0.2 mm, adding the powder into a NaOH solution, soaking the solution for 25-35 minutes, adding Al2O3, stirring the solution, heating the solution at a constant temperature of 60-80° C. for 3-5 hours, cooling the solution to room temperature, washing and drying the obtained solid product, and grinding the obtained solid product into a powder with a particle size of 0.05-0.12 mm to obtain the modified perlite.

6. A sludge dewatering and conditioning method according to claim 5, characterized in that: In the preparation step of the modified perlite, the mass ratio of the expanded perlite, the NaOH solution, and Al2O3 is 0.9-1.1:8-12:1.5-1.7; and the mass fraction of the NaOH solution is 20-30%.

7. A sludge dewatering and conditioning method according to claim 5, characterized in that: In the preparation step of the modified perlite, the particle size of Al2O3 is 0.3-0.5 mm.

8. A sludge dewatering and conditioning method according to claim 1, characterized in that: The sludge conditioning method comprises adjusting the pH value of the sludge to 4-8.5, then adding a sludge conditioner and 3,4-dihydroxybenzoic acid into the sludge, stirring for 8-12 minutes, adding a Na2SO3 solution, and reacting for 50-70 minutes to obtain the conditioned sludge.

9. A sludge dewatering and conditioning method according to claim 8, characterized in that: In the sludge conditioning step, the mass ratio of sludge, sludge conditioner, 3,4-dihydroxybenzoic acid and Na2SO3 solution is 400-420: 0.8-1.2: 2.7-2.8: 3.5-4.0; the mass fraction of the Na2SO3 solution is 28-35%.

10. A sludge dewatering and conditioning method according to claim 1, characterized in that: The filter pressing dehydration method is to filter the conditioned sludge at 0.40-0.50 MPa, and take out the mud cake after 7-9 minutes.

Citation Information

Patent Citations

  • Sludge conditioning method for improving sludge dewatering capacity

    CN113072286A